INN-LogTODIM-GRA Framework for Service Quality Evaluation of International Logistics Enterprises From the Perspective of Cross Border E-Commerce Supply Chain - Huan Zhang; Zimeng Zhu; Jing Wu (IEEE Access, 2023)
In the process of cross-border e-commerce (CBEC) development, CBEC logistics plays a crucial role as a booster. However, the numerous problems exposed in China’s CBEC logistics process have to some extent limited the development of CBEC. Further research on CBEC logistics will guide the healthy development of CBEC platforms. The service quality evaluation of international logistics enterprises from the perspective of CBEC supply chain is a multiple-attribute group decision-making (MAGDM) issue. Recently, the Logarithmic TODIM (LogTODIM) and grey relational analysis (GRA) technique has been employed to come up with MAGDM issues. The interval neutrosophic sets (INSs) are employed as a tool for portraying uncertain decision information during the service quality evaluation of international logistics enterprises from the perspective of CBEC supply chain. In this paper, the interval neutrosophic number Logarithmic TODIM-GRA (INN-LogTODIM-GRA) technique is managed to come up with the MAGDM under INSs. Finally, a numerical example study for service quality evaluation of international logistics enterprises from the perspective of CBEC supply chain is employed to validate the proposed technique. The main contribution of this paper is managed: (1) The information entropy is constructed to obtain weight values under INSs; (2) an integrated INN-LogTODIM-GRA technique is constructed to manage the MAGDM issue; (3) An illustrative example for service quality evaluation of international logistics enterprises from the perspective of EBEC supply chain has accomplished to verify the INN-LogTODIM-GRA technique.